A Case of Endoscopically Treated Laryngopharyngitis Resulting from Clinostomum complanatum Infection - Geum Soo Lee; Sang Wook Park; Jin Kim; Kang Seok Seo; Kyoung Wan You; Jae Hun Chung; Hyeong Chul Moon; Gun Young Hong (The Korean Journal of Gastroenterology, 2017)
A 46-year-old woman visited our hospital presenting throat pain and globus sensation. The symptoms occurred seven days after eating raw perch and mullet. An endoscopy under sedation showed a fluke―with an approximate length of 4.8 mm and width of 1.5 mm―on the left aryepiglottic fold, with active motility on the mucosa. It was extracted from the larynx using biopsy forceps and was identified as Clinostomum complanatum. To the best of our knowledge, this is the second reported case of human infection with Clinostomum complanatum diagnosed and treated by an endoscopy in Korea. Endoscopy is a useful tool in the diagnosis and treatment of patients at risk for parasitic infections complaining of throat pain.